Analisis Investasi Pada Perusahaan Perbankan BUMN Mengunakan ROI, ROA dan ROE Pada Harga Saham Tahun 2021-2025 - Maisye Angelina Sumiok; Regina Izatuisa; Naina Aprillia Syafitri; Tiara Keysha Septiani Putri; Ruth Betania; Mochammad Zulfiqa; Yoyo Sudaryo; Eko Djoko Prabowo (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the effect of Return on Investment (ROI), Return on Assets (ROA), and Return on Equity (ROE) on stock prices of state-owned banking companies listed on the Indonesia Stock Exchange for the period 2021-2025. The research method used is quantitative method with descriptive and verificative approaches. The research sample consists of 5 state-owned banking companies, namely BRI, Bank Mandiri, BNI, BTN, and BSI. The data used are secondary data obtained from annual financial reports of companies and stock price data published on the Indonesia Stock Exchange. Data analysis technique uses multiple linear regression analysis with SPSS 25. The results show that simultaneously ROI, ROA, and ROE have a significant effect on stock prices with a contribution of 33.5%. Partially, ROA has a significant effect on stock prices, while ROI and ROE do not have a significant effect on stock prices. This indicates that ROA is the profitability indicator most considered by investors in making investment decisions on state-owned banking stocks.